New and Convenient Synthesis of Indeno[2,1-c]quinoline Derivatives - Quralshi M.A.; Dhawan S.N. (My University, 2025)
2-Propanoyllndane-1,3-dlone (I) was condensed with aniline and three Isomeric toluldines to give the corresponding anils (Ila-d), which on treatment with polyphosphoric acid afforded the corresponding 6-ethyllndeno[2,1 -c]quinolln-7(7N)-ones (Illa-d). The structures of these were established by elemental analyses and IR and 1H NMR spectral data. © 1989, American Chemical Society. All rights reserved.